Вчення про біосферу — наукова основа її охорони - Стойко, С.М. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2009)
Дан исторический анализ антропогенного/техногенного влияния на субсистемы биосферы (гидро-, педо-, атом-, биото-, социосферу) в отдельные периоды развития общества, рассматриваются его экологические последствия. Обоснована необходимость формирования интегральной науки — геосозологии для охраны биосферы. В ее рамках для охраны отдельных объектов/элементов природы выделен ряд субдисциплин — социальная созология, фитосозология, зоосозология, педосозология, созология ландшафтов и др. Представлены концептуальные положения и приоритетные задачи геосозологии. A historical analysis of anthropogenic/technogenic influence on different subsystems of the biosphere (hydro-, pedo-, atmo-, bioto-, sociosphere) during various periods of development of the human society is presented. A special scientific discipline — geosozology — is substantiated for conservation of biosphere elements. Geosozology is considered as a multidisciplinal science, and, according to the subject of preservation and topics of investigation, the following scientific branches are distinguished: human sozology, phytosozology, zoosozology, pedosozology, landscape sozology, and others. The conceptual principles and priority tasks of geosozology are discussed.